PERANCANGAN BUKU FOTOGRAFI ESAI UNTUK MEMPERKENALKAN JAJANAN TRADISIONAL KHAS JAWA TIMUR BAGI REMAJA USIA 18-25 TAHUN - Putri, Patricia Yuliana Endra; Sukmaraga, Ayyub Anshari; Nugroho, Didit Prasetyo (Ma Chung Press, Universitas Ma Chung, 2024)
Indonesia is rich in traditional cuisine, including that of East Java. With the advancement of time and increasing innovation, the presence of traditional snacks has diminished due to the rise of more varied modern snacks and changing consumer lifestyles. Changes in consumer preferences and the scarcity of raw materials also threaten the preservation of Indonesia's culinary heritage. Furthermore, many young people today prefer fast food that is convenient and visually appealing. However, traditional snacks can be just as enjoyable in terms of taste and presentation, and they carry significant socio-cultural values. Therefore, there is a need for an informational medium that can both introduce traditional snacks and rekindle the interest of teenagers in East Javanese traditional snacks. The design method used is creative communication design, incorporating qualitative data collection. This photo essay book is designed to be 22 x 16 cm in size with 126 full-color pages, bound in a hardcover with a matte lamination. The aim of this photo essay book is to create a visual presentation that introduces various traditional East Javanese snacks through a blend of modern and authentic concepts, using photography complemented by narratives and supporting media such as bookmarks, tote bags, postcards, stickers, tumblers, keyrings, notebooks, t-shirts, posters, banners, desk calendar and marketing through Instagram.